Optimalisasi Kemampuan Bertanya Siswa: Pemberdayaan Guru SMA di Desa Cinta Asih, Karawang - Suryaratri, Ratna; Ariyani, Mira (Jendela Akademika: Jurnal Pengabdian Kepada Masyarakat, 2023)
The paradigm shift in the Indonesian education system where teacher-centered learning is transitioning towards student-centered learning is emphasized in schools. However, many teachers still adhere to the old paradigm in their teaching practices. The main challenges faced are the lack of awareness and difficulties in implementing the new paradigm. The objective of this community empowerment is to change these perceptions through direct classroom training. The focus of the activity at SMA 1 Pangkalan - Karawang is to enhance teachers’ awareness of students’ ability to ask questions and seek academic support in the classroom. The participation of 27 teachers from different levels and subjects in this services resulted findings that significant teaching strategies tailored to students’ needs can encourage student questioning in the classroom. Furthermore, teachers were able to identify students’ needs and provide knowledge and questioning skills that encourage the development of independent learners. The outcomes of this activity include increased teacher awareness of the importance of student questioning behavior, leading to a shift in mindset and departure from the old paradigm. Additionally, it is hoped that this initiative can be sustained in empowering teachers in other areas.